Chronological order in the novel The Rejected by Ibrahim Saadi - Rahim, Abdelkader (El Omda in Linguistics and Discourse Analysis, 2022)
This article is based in its analysis of the chronological order in the novel Al-Marfodone written by the Algerian Ibrahim Saadi on the mechanisms put forward by the French critic Gérard Genette in his Discours du récit, where Genette believes that any narrative text should be studied (in its temporal part) according to one of the three techniques (or all of them): chronological order, duration, or frequency. As the size of the article does not allow for research on the three techniques, the first (chronological order) has been chosen for its remarkable and distinct presence in Al-Marfodone.